Uv curable temporary bonding adhesive and use thereof
Patent Information
- Application Number
- CN202610789912.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-03
- Publication Date
- 2026-10-13
AI Technical Summary
[0007]本发明的目的在于解决现有临时键合胶存在的问题,提供一种UV固化型临时键合胶及其应用
[0019]相对于现有技术,本发明具有以下有益效果。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of advanced semiconductor packaging materials, specifically relating to a UV-curable temporary bonding adhesive and its applications. Background Technology
[0002] In advanced packaging processes such as fan-out wafer-level packaging (FOWLP) and wafer thinning, temporary bonding adhesives are used to temporarily fix the wafer to the carrier substrate to withstand subsequent harsh processes such as etching, cleaning, and heat treatment. Therefore, the adhesive layer is required to have excellent chemical resistance (acid, alkali, and organic solvent resistance), good heat resistance, and sufficient adhesive strength. Simultaneously, after the process is completed, the adhesive layer must be able to be quickly and non-destructively debonded, and after debonding, the adhesive layer must be easy to clean, leaving no residue and not corroding the substrate, thus avoiding affecting subsequent packaging processes and product performance.
[0003] Currently, existing temporary bonding adhesives are mainly classified into UV-curable, thermally debonded, and solvent-debonded types, but they generally suffer from the technical challenge of conflicting chemical resistance and washability. 1. Traditional UV-curable temporary bonding adhesives: To ensure chemical resistance, a resin system with high cross-linking density is usually used, which makes the adhesive layer difficult to dissolve after debonding. It requires cleaning with strong acid, strong alkali or high-energy UV irradiation, which can easily corrode or damage the substrate and leave organic impurities. If the cross-linking density is reduced to improve cleanability, the chemical resistance will be greatly reduced and it will not be able to withstand the harsh processes such as HF etching and NMP cleaning.
[0004] 2. Pyrolytic bond type temporary bonding adhesive: Although it has a certain degree of chemical resistance, the debonding must be carried out under high temperature (usually above 200℃), which can easily cause wafer warping and performance degradation. In addition, carbon residue is easily generated after pyrolysis, requiring an additional ashing treatment process, which is complex and costly.
[0005] 3. Solvent-debonding temporary bonding adhesive: It has good washability, but extremely poor chemical resistance. It is difficult to withstand the immersion in acids, alkalis and organic solvents during the encapsulation process, and the adhesive layer is prone to swelling or peeling, leading to bonding failure.
[0006] In summary, existing temporary bonding adhesives cannot simultaneously meet the core requirements of advanced semiconductor packaging for "high chemical resistance" and "easy cleaning, no residue, and low damage after bonding removal." Therefore, developing a UV-curable temporary bonding adhesive layer resin with excellent chemical resistance, a gentle bonding mechanism, no residue requiring cleaning, and suitable for the environmentally friendly and low-damage requirements of advanced semiconductor packaging has significant industrial value and application prospects. Summary of the Invention
[0007] The purpose of this invention is to solve the problems existing in the current temporary bonding adhesive and to provide a UV-curable temporary bonding adhesive and its application.
[0008] The objective of this invention is achieved through the following technical solution.
[0009] In a first aspect, the present invention provides a UV-curable temporary bonding adhesive, comprising a main resin, an active diluent, a photoinitiator, and additives, wherein the main resin comprises fluorinated polyether segments, o-nitrobenzyl ester structural units, and carbamate oxime structural units.
[0010] Furthermore, the glass transition temperature Tg of the main resin is greater than 120°C.
[0011] Furthermore, after bonding and curing, the UV-curable temporary bonding adhesive has an adhesive strength >8MPa. And / or, unbonding, the adhesive layer's bond strength is less than 0.5 MPa.
[0012] Furthermore, the UV-curable temporary bonding adhesive has a swelling rate of less than 20% after bonding and curing.
[0013] Furthermore, the molar ratio of the fluorinated polyether segment, the o-nitrobenzyl ester structural unit, and the carbamate oxime structural unit is 1:(0.12~0.5):(0.16~0.44).
[0014] Furthermore, the fluorinated polyether segment is derived from a fluorinated polyether polyol, and the fluorinated polyether polyol is selected from at least one of perfluorinated polyether diol, semifluorinated polyether diol, and side-chain fluorinated polyether diol.
[0015] Furthermore, the o-nitrobenzyl ester structural unit is derived from hydroxyl-containing o-nitrobenzyl ester monomers, wherein the hydroxyl-containing o-nitrobenzyl ester monomers are selected from at least one of 2-nitro-4-hydroxybenzyl acrylate and 2-nitro-4-hydroxybenzyl methacrylate.
[0016] Furthermore, the carbamate oxime structural unit is obtained by reacting a dioxime monomer with an isocyanate monomer, wherein the dioxime monomer is selected from at least one of dimethylglyoxime, 1,4-benzoquinone dioxime, dichloroglyoxime, glutaraldehyde dioxime, and 1,2-cyclohexanedione dioxime.
[0017] Furthermore, the mass ratio of the main resin, reactive diluent, photoinitiator, and additives is (60~70):(15~25):(2.5~4):(0.15~0.4).
[0018] In a second aspect, the present invention provides the application of the UV-curable temporary bonding adhesive as described in the first aspect, wherein the UV-curable temporary bonding adhesive is used in wafer processing for temporary bonding and debonding.
[0019] Compared with the prior art, the present invention has the following beneficial effects.
[0020] The UV-curable temporary bonding adhesive of this invention uses fluorinated dynamic polyurethane acrylate (F-DPUA) as the main resin. The molecular structure of the main resin simultaneously contains fluorinated chemical-resistant segments, o-nitrobenzyl ester structural units (UV photo-cleaving bonds), and carbamate oxime structural units (thermally reversible dynamic bonds). After curing, it forms a highly chemical-resistant cross-linked network that can withstand the harsh processes of semiconductor packaging. During bond unbonding, it is triggered by both ultraviolet (UV) light and dilute alkaline hot water, resulting in non-destructive peeling and complete dissolution of the adhesive layer, leaving no residue and not corroding the substrate, thus achieving a synergy between chemical resistance and washability.
[0021] The UV-curable temporary bonding adhesive of this invention has a mild and environmentally friendly debonding mechanism. The debonding process does not require high temperature (maximum 80°C) or strong acid or alkali (only 0.5% TMAH dilute alkaline water is used), and no harmful gases or carbon residues are generated. It is suitable for the environmental protection and low damage requirements of semiconductor packaging, reducing process costs and environmental burden.
[0022] The UV-curable temporary bonding adhesive of this invention has a fast UV curing speed, high bonding strength, and simple debonding and cleaning steps. It can be directly integrated into existing semiconductor packaging production lines without modifying existing equipment, making it easy to promote industrialization.
[0023] UV-curable temporary bonding adhesives can be used not only in advanced semiconductor packaging, including FOWLP (fan-out wafer-level packaging) and 2.5D / 3D packaging, but also in other microelectronic manufacturing processes that require temporary bonding and have high requirements for chemical resistance and cleanability. Detailed Implementation
[0024] To make the technical problems solved, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the embodiments described herein are only some, not all, of the embodiments of this invention, and are merely illustrative and not intended to limit the invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the protection scope of this invention.
[0025] In a first aspect, the present invention provides a temporary bonding adhesive comprising a host resin, an active diluent, a photoinitiator, and an additive, wherein the host resin comprises fluorinated polyether segments, o-nitrobenzyl ester structural units, and carbamate oxime structural units.
[0026] Fluorinated polyether segments possess extremely low surface energy and excellent resistance to acids, alkalis, and organic solvents. As the core component of the resin backbone, they form a chemical barrier, ensuring that the cured adhesive layer can withstand the stringent processes in semiconductor packaging. The o-nitrobenzyl ester structural unit has UV photolytic bonds, exhibiting high sensitivity to 365nm UV light. Upon UV irradiation, it can rapidly break down, causing a sharp drop in adhesive layer strength and slight volume expansion, achieving non-destructive peeling of the adhesive layer from the substrate. The oxime carbamate structural unit has thermally reversible dynamic bonds, which can undergo hydrolytic breakage in a dilute alkaline water environment at 60~80℃, causing the peeled adhesive layer network to completely disintegrate and transform into easily soluble fluorinated oligomers, achieving residue-free cleaning.
[0027] In some specific embodiments, the glass transition temperature Tg of the main resin is greater than 120°C, which enables the bonding adhesive to maintain a certain hardness and strength under high temperature conditions, thus avoiding the problem of performance degradation or failure of the bonding adhesive due to high temperature in subsequent processes.
[0028] In some specific embodiments, after the UV-curable temporary bonding adhesive is bonded and cured, the adhesive layer has a bonding strength >8MPa, indicating that the UV-curable temporary bonding adhesive can firmly bond the wafer and the substrate, and avoid the wafer and the substrate from debonding due to shearing during the wafer thinning process.
[0029] In some specific embodiments, the bonding is debonded, the adhesive layer has a bonding strength of less than 0.5 MPa, and the wafer and the substrate can be automatically separated, making the bonding adhesive easy to remove from the wafer after the wafer fabrication process is completed.
[0030] In some specific embodiments, the UV-curable temporary bonding adhesive has a swelling rate of less than 20% after bonding and curing.
[0031] In some specific embodiments, the molar ratio of the fluorinated polyether segment, the o-nitrobenzyl ester structural unit, and the carbamate oxime structural unit is 1:(0.12~0.5):(0.16~0.44). This achieves a better balance between the chemical resistance, gentle debonding mechanism, and residue-free cleaning of the temporary bonding adhesive, meeting the environmental protection and low-damage requirements of advanced semiconductor packaging. In this application, the molar ratio of each structural unit refers to the molar ratio of the monomers used to generate each structural unit.
[0032] In some specific embodiments, the fluorinated polyether segments are derived from fluorinated polyether polyols, which are selected from at least one of perfluoropolyether diols, semi-fluorinated polyether diols, and side-chain fluorinated polyether diols, preferably perfluoropolyether diols. More specifically, the semi-fluorinated polyether diol has the structural formula OH-[CHF-CHF-O-]. n -H, the structural formula of the fluorinated polyether diol with side chain is OH-[CH(-CF3)-CH(-CF3)-O-]n -H; Fluorinated polyether segments have extremely low surface energy and excellent resistance to acids, alkalis and organic solvents. As the core part of the resin backbone, they form a chemical barrier to ensure that the cured adhesive layer can withstand the harsh processes in semiconductor packaging.
[0033] In some specific embodiments, the o-nitrobenzyl ester structural unit is derived from a hydroxyl-containing o-nitrobenzyl ester monomer, which is selected from at least one of 2-nitro-4-hydroxybenzyl acrylate and 2-nitro-4-hydroxybenzyl methacrylate. The o-nitrobenzyl ester bond in the o-nitrobenzyl ester structural unit is highly sensitive to 365nm UV light and can break rapidly after UV irradiation, causing a sharp drop in adhesive layer strength and slight volume expansion, thus achieving non-destructive peeling of the adhesive layer from the substrate.
[0034] In some specific embodiments, the carbamate oxime structural unit is obtained by reacting a dioxime monomer with an isocyanate monomer. The dioxime monomer is selected from at least one of dimethylglyoxime, 1,4-benzoquinone dioxime, dichloroglyoxime, glutaraldehyde dioxime, and 1,2-cyclohexanedione dioxime. The isocyanate monomer is selected from hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), toluene diisocyanate (TDI), and diphenylmethane diisocyanate (MDI), preferably isophorone diisocyanate (IPDI). The carbamate oxime bond formed by the reaction of the dioxime monomer and the isocyanate monomer can undergo hydrolytic cleavage in a dilute alkaline water environment at 60-80°C, causing the peeled adhesive network to completely disintegrate and transform into easily soluble fluorinated oligomers, achieving residue-free cleaning.
[0035] The main resin in the UV-curable temporary bonding adhesive of this invention can be obtained through the following steps: (1) Prepolymerization reaction: Fluorinated polyether polyol is mixed with isocyanate monomers, and dibutyltin dilaurate (DBTL) is added as a catalyst. The prepolymerization reaction is carried out at 60~80℃ for 2~3 hours to generate -NCO-terminated fluorinated polyurethane prepolymer; the equivalent ratio of -NCO groups in isocyanate monomers to -OH groups in fluorinated polyether polyol is (1.2~1.5):1, and the amount of catalyst is 0.1~0.3% of the total mass of fluorinated polyether polyol; (2) Chain extension reaction: Dioxime monomers are added to the fluorinated polyurethane prepolymer obtained in step (1) as chain extenders, and the reaction is continued at 60~70℃ for 1~2 hours to generate chain extension products containing carbamate oxime bonds. By controlling the amount of dioxime monomers added, the molecular weight of the product is controlled at 5000~8000. By controlling the molecular weight of the product, on the one hand, the final UV-curable temporary bonding adhesive has a suitable viscosity, so that it can obtain the target thickness adhesive layer on the wafer surface through homogenization. On the other hand, the cured bonding adhesive has sufficient strength to meet the shear resistance requirements of the wafer in the subsequent back grinding process. The molar ratio of dioxime monomers to fluorinated polyether polyols is (0.16~0.44):1. (3) End-capping reaction: Add hydroxyl-containing o-nitrobenzyl ester monomers to the chain extension product obtained in step (2), react at 50~60℃ for 1~1.5 hours, end-cap the remaining -NCO groups, introduce UV-crackable o-nitrobenzyl ester bonds, and obtain fluorinated dynamic polyurethane acrylate (F-DPUA), i.e. the main resin; wherein, the molar ratio of hydroxyl-containing o-nitrobenzyl ester monomers to fluorinated polyether polyols is (0.12~0.5):1.
[0036] Preferably, before the prepolymerization reaction in step (1), dimethylolpropionic acid (DMPA) can be added and mixed with fluorinated polyether polyol at an amount of 0.5% to 1% of the mass of fluorinated polyether polyol, and then mixed with isocyanate. DMPA can better promote the solubility of the decomposed glue in water during debonding. After the end-capping reaction in step (3), triethylamine needs to be added to the product obtained in step (3) for neutralization reaction. The amount of triethylamine is 0.5% to 1% of the mass of fluorinated polyether polyol. Stir at room temperature for 30 to 60 minutes to neutralize the carboxyl groups of DMPA in the system and adjust the pH of the system to 7 to 8, thereby obtaining fluorinated dynamic polyurethane acrylate (F-DPUA), which is the main resin.
[0037] In some specific embodiments, the mass ratio of the main resin, reactive diluent, photoinitiator, and additives is (60~70):(15~25):(2.5~4):(0.15~0.4). Specifically, the mass ratio of the main resin, reactive diluent, photoinitiator, and additives is 60:15:2.5:0.15, 62:18:3:0.2, 64:18:3:0.25, 65:20:3.3:0.28, 67:22:3.4:0.3, 68:23:3.5:0.36, or 70:25:4:0.4, etc.
[0038] The base resin, as the main component of UV-curable temporary bonding adhesives, primarily provides chemical resistance, dynamic debonding properties, and adhesive performance. The reactive diluent enhances the chemical resistance of the adhesive layer, reduces surface energy, and regulates the crosslinking density, balancing adhesive strength and curing speed. The photoinitiator triggers the UV curing reaction and enhances the UV cleavage efficiency of o-nitrobenzyl ester bonds, shortening the debonding time. Additives improve the coating performance of the adhesive, preventing defects such as edge shrinkage and pinholes, and preventing self-polymerization during storage and processing. When the base resin, reactive diluent, photoinitiator, and additives meet the appropriate mass ratios, the overall performance of the UV-curable temporary bonding adhesive, including chemical resistance, heat resistance, adhesion, curing properties, and debonding ability, is optimal.
[0039] In some specific embodiments, the reactive diluent includes perfluorohexyl ethyl acrylate and / or trimethylolpropane triacrylate.
[0040] In some specific embodiments, the photoinitiator includes a photolysis initiator and / or an o-nitrobenzyl ester bond sensitizer.
[0041] In some specific embodiments, the additives include leveling agents and / or polymerization inhibitors.
[0042] Perfluorohexyl ethyl acrylate (FHEA) in reactive diluents enhances the chemical resistance and low surface energy of the adhesive layer, while trimethylolpropane triacrylate (TMPTA) adjusts the crosslinking density of the adhesive layer, balancing bond strength and curing speed. Photoinitiators, such as photolysis initiators (e.g., Irgacure 184), trigger the UV curing reaction, while o-nitrobenzyl ester bond sensitizers (e.g., Irgacure 2959) enhance the UV cleavage efficiency of o-nitrobenzyl ester bonds, shortening the debonding time. Additives, such as leveling agents (e.g., BYK-333), improve the coating performance of the adhesive, preventing defects such as edge shrinkage and pinholes, while polymerization inhibitors (e.g., p-hydroxyanisole) prevent self-polymerization of the adhesive during storage and processing.
[0043] Preferably, the reactive diluent comprises perfluorohexyl ethyl acrylate (FHEA) and trimethylolpropane triacrylate (TMPTA), wherein the mass ratio of FHEA to TMPTA is (1.3~3):1; specifically, the mass ratio of FHEA to TMPTA can be 1.3:1, 1.5:1, 1.6:1, 1.8:1, or 2:1, etc. A suitable mass ratio optimizes chemical resistance, surface finish, crosslinking density, adhesive strength, and curing speed.
[0044] The photoinitiator comprises a photolysis initiator and an o-nitrobenzyl ester bond sensitizer. The mass ratio of the photolysis initiator (e.g., Irgacure 184) to the o-nitrobenzyl ester bond sensitizer (e.g., Irgacure 2959) is (2~6):1. Specifically, the mass ratio of the photolysis initiator to the o-nitrobenzyl ester bond sensitizer can be 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, or 6:1, etc. A suitable mass ratio results in higher UV curing reaction efficiency.
[0045] The additives include leveling agents and polymerization inhibitors, with the mass ratio of the leveling agent (e.g., BYK-333) to the polymerization inhibitor (e.g., p-hydroxyanisole) being (1.2~3):1; specifically, the mass ratio of the leveling agent to the polymerization inhibitor can be 1.2:1, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.7:1, or 3:1, etc. A suitable mass ratio results in higher coating performance and reduces the likelihood of self-polymerization.
[0046] The preparation of the UV-curable temporary bonding adhesive of the present invention can be carried out by the following steps: weigh the main resin, reactive diluent, photoinitiator and additives according to the above mass ratio, stir at 25°C and 300 r / min for 30 minutes, mix evenly, and filter with a 0.22 μm filter membrane to obtain the UV-curable temporary bonding adhesive.
[0047] In a second aspect, the present invention provides the application of the UV-curable temporary bonding adhesive as described in the first aspect, wherein the UV-curable temporary bonding adhesive is used in wafer processing for temporary bonding and debonding.
[0048] The UV-curable temporary bonding adhesive of this invention can achieve "UV bonding curing - UV-triggered debonding - removal by dilute alkaline hot water washing", as detailed below: (1) UV bonding and curing: The UV-curable temporary bonding adhesive of the present invention is uniformly coated onto the surface of the substrate to be bonded (such as a silicon wafer) by spin coating or blade coating; then it is irradiated with 365nm UV light (such as a high-pressure mercury lamp) with a UV energy of 800~1200mJ / cm 2 The irradiation time is 30-60 seconds to complete the bonding and curing. After curing, the adhesive layer has a bond strength >8MPa, indicating that the UV-curable temporary bonding adhesive can firmly bond the wafer and the substrate, preventing the wafer and substrate from delaminating due to shearing during the wafer thinning process. The adhesive layer can withstand an environment of 250℃ for 20-40 minutes, and after immersion in common process solvents (such as 25% TMAH, 49% HF, concentrated sulfuric acid, NMP, etc.) for 24 hours, the swelling rate is less than 20% and there is no peeling.
[0049] (2) UV-triggered debonding: After the process is completed, that is, after wafer back-side grinding, wiring, TSV (through silicon via), reflow soldering ball placement and other processes, the adhesive layer is cured by irradiation with 365nm UV light, and the UV energy is 3000~5000 mJ / cm 2 The irradiation time is 1-2 minutes. During this time, the ortho-nitrobenzyl bonds in the adhesive layer break, the cross-linking network of the adhesive layer is destroyed, and the bonding strength drops below 0.5 MPa. The adhesive layer automatically lifts off, achieving non-destructive peeling from the substrate. With the bonding strength of the debonded adhesive layer dropping below 0.5 MPa, the wafer and carrier can automatically separate, making the bonding adhesive easy to remove from the wafer after the wafer fabrication process is completed.
[0050] (3) Removal by dilute alkaline hot water cleaning: Place the warped adhesive layer in a 0.5% tetramethylammonium hydroxide (TMAH) aqueous solution at 60~80℃ and treat it by soaking or spraying for 5~10 minutes; at this time, the carbamate oxime bonds in the adhesive layer are hydrolyzed and broken, and the adhesive layer network is completely disintegrated into fluorinated oligomers. The fluorinated oligomers dissolve rapidly in the dilute alkaline aqueous solution. Then rinse the substrate surface with deionized water to complete the cleaning without residue. The contact angle of the substrate surface is about 10~15°, restoring it to the intrinsic level of the silicon wafer.
[0051] The specific embodiments of the present invention will be further explained and described below through examples and comparative examples.
[0052] Unless otherwise specified, all reagents, materials, and instruments used in the following description are conventional reagents, materials, and instruments, all of which are commercially available. The reagents involved can also be synthesized using conventional synthetic methods. Unless otherwise specified, the methods in the examples are conventional methods in the art.
[0053] Example 1 1) Preparation of the main resin Before the prepolymerization reaction, 0.8 g of dimethylolpropionic acid (DMPA) and 100 g of perfluoropolyether diol (PFPE-diol, Mn=1000) were added and mixed. Then, 28.6 g of isophorone diisocyanate (IPDI, 222 g / mol) was added and stirred evenly. Then, 0.13 g of dibutyltin dilaurate (DBTL) was added, the temperature was raised to 70 °C, and the reaction was kept at a constant temperature for 2.5 hours to obtain -NCO-terminated fluorinated polyurethane prepolymer. 1.856 g of dimethylglyoxime (DMG, 116 g / mol) was added to the fluorinated polyurethane prepolymer, and the reaction was continued at 70 °C for 1.5 hours to obtain a chain-extended product containing carbamate oxime ester bonds with a molecular weight of 6500. 2.676 g of 2-nitro-4-hydroxybenzyl acrylate (223 g / mol) was added to the chain extension product, the temperature was lowered to 55 °C, and the reaction was carried out for 1.2 hours to end-cap the remaining -NCO groups and introduce o-nitrobenzyl ester bonds. Finally, 0.6 g of triethylamine was added, and the mixture was stirred at room temperature for 45 minutes to neutralize the carboxyl groups of DMPA in the system. The pH was then adjusted to 7.5 to obtain the fluorinated dynamic polyurethane acrylate (F-DPUA) prepolymer, which is the main resin. The molar ratio of fluorinated polyether segments, o-nitrobenzyl ester structural units, and carbamate oxime structural units in this main resin is 1:0.12:0.16.
[0054] 2) Preparation of UV-curable temporary bonding adhesive Weigh the following components by weight: 65 parts of base resin (F-DPUA), 12 parts of perfluorohexyl ethyl acrylate (FHEA), 8 parts of trimethylolpropane triacrylate (TMPTA), 2.5 parts of Irgacure 184, 0.8 parts of Irgacure 2959, 0.2 parts of BYK-333, and 0.08 parts of p-hydroxyanisole. Add the above components to a mixing tank and stir for 30 minutes at 25°C and 300 rpm. After mixing evenly, filter through a 0.22 μm filter membrane to obtain a UV-curable temporary bonding adhesive.
[0055] 3) Application of UV-curable temporary bonding adhesives UV bonding curing: The prepared UV-curable temporary bonding adhesive was spin-coated onto the silicon wafer surface to a thickness of 8 μm, and then irradiated with 365 nm UV light at a UV energy of 1000 mJ / cm². 2 The bonding and curing process was completed after 45 seconds of irradiation. The adhesive layer after curing had a bond strength of 8.3 MPa and a Tg of 153℃. It showed no deformation or peeling after being placed at 250℃ for 30 minutes. After immersion in 25% TMAH, 49% HF, concentrated sulfuric acid, and NMP solvents for 24 hours, the adhesive layer showed no swelling or peeling, demonstrating excellent chemical resistance.
[0056] UV-triggered debonding: The cured adhesive layer was irradiated with 365nm UV light at a UV energy of 4000 mJ / cm². 2 After irradiation for 2.6 minutes, the adhesive strength of the adhesive layer dropped to 0.3 MPa, causing it to automatically lift and peel off from the silicon wafer without damage.
[0057] Removed by dilute alkaline hot water cleaning: Place the peeled adhesive layer in a 70℃, 0.5% (w / w) tetramethylammonium hydroxide (TMAH) aqueous solution and soak for 8 minutes. The adhesive layer will completely dissolve. Rinse the silicon wafer surface with deionized water. There will be no adhesive residue. The contact angle of the silicon wafer surface will be 12°, restoring it to its intrinsic level.
[0058] Example 2 This embodiment uses most of the operating steps described in Example 1 to prepare the host resin and UV-curable temporary bonding adhesive. The main difference is that in the preparation of the host resin, the amount of dimethylglyoxime added is 5.104 g, and the amount of 2-nitro-4-hydroxybenzyl acrylate added is 11.15 g. The molar ratio of fluorinated polyether segments, o-nitrobenzyl ester structural units, and carbamate oxime structural units in the host resin is 1:0.5:0.44.
[0059] Example 3 1) Preparation of the main resin 100g of perfluoropolyether diol (PFPE-diol, Mn=1000) and 28.6g of isophorone diisocyanate (IPDI, 222g / mol) were mixed and stirred evenly, and then 0.13g of dibutyltin dilaurate (DBTL) was added. The mixture was heated to 70℃ and reacted at a constant temperature for 2.5 hours to obtain -NCO-terminated fluorinated polyurethane prepolymer. 8.8 g of dimethylglyoxime (DMG, 116 g / mol) was added to the fluorinated polyurethane prepolymer, and the reaction was continued at 70 °C for 1.5 hours to obtain a chain-extended product containing carbamate oxime ester bonds with a molecular weight of 7000. 16.4 g of 2-nitro-4-hydroxybenzyl acrylate (223 g / mol) was added to the chain extender, the mixture was cooled to 55 °C, and reacted for 1.2 hours. The remaining -NCO groups were capped to introduce o-nitrobenzyl ester bonds, yielding a fluorinated dynamic polyurethane acrylate (F-DPUA) prepolymer, which serves as the main resin. The molar ratio of fluorinated polyether segments, o-nitrobenzyl ester structural units, and carbamate oxime structural units in this main resin is 1:0.735:0.76.
[0060] 2) Preparation of UV-curable temporary bonding adhesive Weigh the following components by weight: 65 parts of base resin (F-DPUA), 12 parts of perfluorohexyl ethyl acrylate (FHEA), 8 parts of trimethylolpropane triacrylate (TMPTA), 2.5 parts of Irgacure 184, 0.8 parts of Irgacure 2959, 0.2 parts of BYK-333, and 0.08 parts of p-hydroxyanisole. Add the above components to a mixing tank and stir for 30 minutes at 25°C and 300 rpm. After mixing evenly, filter through a 0.22 μm filter membrane to obtain a UV-curable temporary bonding adhesive.
[0061] 3) Application of UV-curable temporary bonding adhesives UV bonding curing: The prepared UV-curable temporary bonding adhesive was spin-coated onto the silicon wafer surface to a thickness of 8 μm, and then irradiated with 365 nm UV light at a UV energy of 1000 mJ / cm².2 The bonding and curing process was completed after 45 seconds of irradiation. The adhesive layer after curing had a bond strength of 9.2 MPa and a Tg of 128℃. It showed no deformation or peeling after being placed at 250℃ for 30 minutes. After being immersed in 25% TMAH, 49% HF, concentrated sulfuric acid, and NMP solvents for 24 hours, the adhesive layer showed no swelling or peeling, demonstrating excellent chemical resistance.
[0062] UV-triggered debonding: The cured adhesive layer was irradiated with 365nm UV light at a UV energy of 4000 mJ / cm². 2 After 1.5 minutes of irradiation, the adhesive strength of the adhesive layer dropped to 0.3 MPa, causing it to automatically lift and peel off from the silicon wafer without damage.
[0063] Removed by dilute alkaline hot water cleaning: Place the peeled adhesive layer in a 70℃, 0.5% (w / w) tetramethylammonium hydroxide (TMAH) aqueous solution and soak for 8 minutes. The adhesive layer will completely dissolve. Rinse the silicon wafer surface with deionized water. There will be no adhesive residue. The contact angle of the silicon wafer surface will be 12°, restoring it to its intrinsic level.
[0064] Example 4 This embodiment uses most of the operating steps described in Example 1 to prepare the host resin and UV-curable temporary bonding adhesive. The main difference is that in the preparation of the host resin, the amount of hydroxyl-containing o-nitrobenzyl ester is 5.1 g of 2-nitro-4-hydroxybenzyl methacrylate (237 g / mol), and the amount of dimethylglyoxime added is 8.8 g, with the rest being the same as in Example 1. The molar ratio of fluorinated polyether segments, o-nitrobenzyl ester structural units, and carbamate oxime structural units in this host resin is 1:0.2:0.76.
[0065] Example 5 This embodiment uses most of the operating steps in Example 1 to prepare the main resin and UV-curable temporary bonding adhesive. The main difference is that in the preparation of the main resin, the fluorinated polyether polyol is a semi-fluorinated polyether diol (Mn=1000), and its molar amount is the same as that of the perfluorinated polyether diol in the example.
[0066] Example 6 This embodiment uses most of the operating steps in Example 1 to prepare the host resin and UV-curable temporary bonding adhesive. The main difference is that in the preparation of the host resin, the dioxime monomer is 1,4-benzoquinone dioxime, and the molar amount of 1,4-benzoquinone dioxime is the same as that of dimethylglyoxime in Example 1.
[0067] Example 7 This embodiment uses most of the operating steps described in Example 1 to prepare the host resin and UV-curable temporary bonding adhesive. The main difference lies in the composition of the UV-curable temporary bonding adhesive: 70 parts host resin (F-DPUA), 15 parts perfluorohexyl ethyl acrylate (FHEA), 10 parts trimethylolpropane triacrylate (TMPTA), 3 parts Irgacure 184, 1 part Irgacure 2959, 0.3 parts BYK-333, and 0.1 parts p-hydroxyanisole.
[0068] Example 8 This embodiment uses most of the operating steps described in Example 1 to prepare the host resin and UV-curable temporary bonding adhesive. The main difference lies in the composition of the UV-curable temporary bonding adhesive: 60 parts host resin (F-DPUA), 10 parts perfluorohexyl ethyl acrylate (FHEA), 5 parts trimethylolpropane triacrylate (TMPTA), 2 parts Irgacure 184, 0.5 parts Irgacure 2959, 0.1 parts BYK-333, and 0.05 parts p-hydroxyanisole.
[0069] Example 9 This embodiment uses most of the operating steps described in Example 1 to prepare the host resin and UV-curable temporary bonding adhesive. The main difference lies in the composition of the UV-curable temporary bonding adhesive: 65 parts host resin (F-DPUA), 15 parts perfluorohexyl ethyl acrylate (FHEA), 5 parts trimethylolpropane triacrylate (TMPTA), 2.4 parts Irgacure 184, 0.6 parts Irgacure 2959, 0.18 parts BYK-333, and 0.1 parts p-hydroxyanisole.
[0070] Comparative Example 1 The UV-curable temporary bonding adhesive of this comparative example is a conventional UV-curable temporary bonding adhesive, using ordinary polyurethane acrylate as the main resin. The main resin does not contain fluorinated polyether segments, o-nitrobenzyl ester bonds, and carbamate oxime bonds. The remaining components are the same as in Example 1. The temporary bonding adhesive was prepared and its performance was tested.
[0071] The results showed that the adhesive strength of the cured adhesive layer was 7.8 MPa, and swelling and detachment occurred after soaking in 25% TMAH aqueous solution for 24 hours. After debonding, it was necessary to soak in concentrated nitric acid for 30 minutes to remove the adhesive layer, and there was obvious residual adhesive and obvious corrosion marks on the silicon wafer surface.
[0072] Comparative Example 2 The temporary bonding adhesive of this comparative example uses existing pyrolytic polyurethane resin as the main resin, and the other components are the same as those in Example 1. The temporary bonding adhesive was prepared and its performance was tested.
[0073] The results showed that the cured adhesive layer had good chemical resistance, but the debonding required heating at 220℃ for 60 minutes, and the silicon wafer showed slight warping. There was carbon residue after debonding, which required ashing treatment, making the process complicated and causing slight damage to the silicon wafer surface.
[0074] Comparative Example 3 In this comparative example, the main resin of the UV-curable temporary bonding adhesive did not contain dimethylglyoxime during preparation, and the main resin did not contain carbamate oxime structural units; otherwise, it was the same as in Example 1.
[0075] Comparative Example 4 In the preparation of the UV-curable temporary bonding adhesive of this comparative example, no hydroxyl-containing o-nitrobenzyl esters were added to the main resin, and the main resin did not contain o-nitrobenzyl ester structural units. Otherwise, it was the same as in Example 1.
[0076] Performance testing: To better understand the present invention, the temporary bonding adhesives of the above embodiments and comparative examples were subjected to the following performance tests.
[0077] The prepared temporary bonding adhesive was spin-coated onto the surface of a silicon wafer to a thickness of 8 μm. The wafer was then irradiated with 365 nm UV light at a UV energy of 1000 mJ / cm² for 45 seconds to complete the bonding and curing process.
[0078] Refer to GB / T 2790-1995 national standard to test the adhesive strength of the bonded and cured adhesive layer.
[0079] The glass transition temperature (Tg) of the bulk resin was tested using a dynamic thermomechanical analyzer (DMA).
[0080] After being placed at 250℃ for 30 minutes, the adhesive layer was visually inspected for deformation or peeling to test its high-temperature resistance.
[0081] Swelling and shedding tests of the adhesive layer: After peeling the adhesive layer from the silicon wafer, it was immersed in 25% TMAH, 49% HF, concentrated sulfuric acid and NMP solvent respectively. After immersion at 25±2℃ for 24 hours, the adhesive layer was visually observed to see if it had detached. The weight of the adhesive film before and after immersion was weighed to calculate whether it swelled and to test its chemical resistance. The test results were summarized and recorded in Table 1.
[0082] Table 1 After the temporary bonding adhesives of the above embodiments and comparative examples were processed, the cured adhesive layers were irradiated with 365nm UV light with a UV energy of 4000 mJ / cm². 2 UV irradiation was used to debond the adhesive, and the debonding time was recorded. The adhesive strength of the adhesive layer after debonding was tested in accordance with GB / T 2790-1995 national standard.
[0083] The peeled adhesive layer was placed in a 70°C, 0.5% (w / w) tetramethylammonium hydroxide (TMAH) aqueous solution and soaked until the adhesive layer was completely dissolved. The dissolution time was recorded. The silicon wafer surface was then rinsed with deionized water to remove the adhesive.
[0084] By comparing the elemental composition and proportion of the original silicon wafer and the debonded silicon wafer surface using EDS elemental analysis under an electron microscope, it can be determined whether there is residual adhesive on the silicon wafer surface.
[0085] The contact angle of the silicon wafer surface was measured using a contact angle tester. The test solution was the UV-curable temporary bonding adhesive described in this patent. The test results, including the bond strength of the debonded adhesive layer and the cleaning effect, are summarized in Table 2.
[0086] Table 2 As shown in Tables 1 and 2, when the molar ratio of the fluorinated polyether segments, o-nitrobenzyl ester structural units, and carbamate oxime structural units is 1:(0.12~0.5):(0.16~0.44), the adhesive layer exhibits a bonding strength >8MPa and a glass transition temperature Tg >120℃ after bonding and curing. It withstands 250℃ for 20~40 minutes and exhibits a swelling rate of less than 20% and no detachment after immersion in common process solvents for 24 hours. During debonding, the adhesive layer's bonding strength drops below 0.5MPa under UV irradiation, automatically lifting off and debonding within 1~3 minutes, peeling off without damage from the silicon wafer. After soaking in dilute alkaline hot water, the adhesive layer completely dissolves and disintegrates. Rinsing the silicon wafer surface with deionized water leaves no residue, and the substrate surface contact angle is approximately 10~15°, restoring it to the intrinsic level of the silicon wafer. This indicates that the UV-curable temporary bonding adhesive of this application does not corrode the substrate. If the molar ratio of the fluorinated polyether segment, the o-nitrobenzyl ester structural unit and the carbamate oxime structural unit is not within the range disclosed in this application (Examples 3 and 4), the debonding and cleaning effects are basically unaffected, but the high temperature resistance and chemical resistance are slightly worse. There will be slight deformation at 250°C and 15% swelling in the solvent, but there is no shedding at high temperature or in the solvent.
[0087] As can be seen from the comparison of the embodiments with Comparative Examples 1 and 2, the temporary bonding adhesive layer of the present invention is significantly superior to the prior art in terms of chemical resistance, debonding temperature and gentleness, and washability.
[0088] A comparison of the examples with Comparative Examples 3 and 4 shows that fluorinated chemical-resistant segments can improve the bonding strength and glass transition temperature of the adhesive layer after temporary bonding and curing, enhancing high-temperature resistance and chemical resistance. Thermally reversible dynamic bonds can undergo hydrolytic breakage in dilute alkaline hot water, completely disintegrating the peeled adhesive network, promoting complete dissolution of the adhesive layer, and achieving residue-free cleaning. UV-photolytic bonds can rapidly break after UV irradiation, causing a sharp drop in adhesive layer strength and slight volume expansion, achieving non-destructive peeling of the adhesive layer from the substrate. Fluorinated chemical-resistant segments, UV-photolytic bonds, and thermally reversible dynamic bonds are all indispensable; otherwise, chemical resistance will deteriorate, bonding may fail, or cleaning may leave residue.
[0089] This invention perfectly resolves the contradiction between chemical resistance and cleanability. After bonding and curing, it forms a highly chemical-resistant cross-linked network that can withstand the stringent processes of semiconductor packaging. The adhesive layer can be peeled off without damage and completely dissolved, leaving no residue and not corroding the substrate. It balances chemical resistance and easy cleaning, meeting the environmental protection and low-damage requirements of semiconductor packaging, and reducing process costs and environmental burden.
[0090] The present invention has been further described above with reference to specific embodiments. However, it should be understood that the specific description herein should not be construed as limiting the nature and scope of the present invention. Various modifications made to the above embodiments by those skilled in the art after reading this specification are all within the scope of protection of the present invention.
Claims
1. A UV-curable temporary bonding adhesive, characterized in that, The UV-curable temporary bonding adhesive includes a main resin, an active diluent, a photoinitiator, and additives. The main resin includes fluorinated polyether segments, o-nitrobenzyl ester structural units, and carbamate oxime structural units.
2. The UV-curable temporary bonding adhesive according to claim 1, characterized in that, The glass transition temperature (Tg) of the main resin is greater than 120°C.
3. The UV-curable temporary bonding adhesive according to claim 1, characterized in that, After bonding and curing, the adhesive layer of the UV-curable temporary bonding adhesive has a bonding strength >8MPa. And / or, unbonding, the adhesive layer's bond strength is less than 0.5 MPa.
4. The UV-curable temporary bonding adhesive according to claim 1, characterized in that, The UV-curable temporary bonding adhesive has a swelling rate of less than 20% after bonding and curing.
5. The UV-curable temporary bonding adhesive according to any one of claims 1 to 4, characterized in that, The molar ratio of the fluorinated polyether segment, the o-nitrobenzyl ester structural unit, and the carbamate oxime structural unit is 1:(0.12~0.5):(0.16~0.44).
6. The UV-curable temporary bonding adhesive according to claim 1, characterized in that, The fluorinated polyether segments are derived from fluorinated polyether polyols, which are selected from at least one of perfluorinated polyether diols, semifluorinated polyether diols, and side-chain fluorinated polyether diols.
7. The UV-curable temporary bonding adhesive according to claim 1, characterized in that, The o-nitrobenzyl ester structural unit is derived from hydroxyl-containing o-nitrobenzyl ester monomers, which are selected from at least one of 2-nitro-4-hydroxybenzyl acrylate and 2-nitro-4-hydroxybenzyl methacrylate.
8. The UV-curable temporary bonding adhesive according to claim 1, characterized in that, The carbamate oxime ester structural unit is obtained by reacting a dioxime monomer with an isocyanate monomer, wherein the dioxime monomer is selected from at least one of dimethylglyoxime, 1,4-benzoquinone dioxime, dichloroglyoxime, glutaraldehyde dioxime, and 1,2-cyclohexanedione dioxime.
9. The UV-curable temporary bonding adhesive according to claim 1, wherein the mass ratio of the main resin, reactive diluent, photoinitiator and additives is (60~70):(15~25):(2.5~4):(0.15~0.4).
10. An application of the UV-curable temporary bonding adhesive as described in any one of claims 1 to 9, characterized in that, The UV-curable temporary bonding adhesive is used in wafer fabrication for temporary bonding and debonding.